Evaluation and Improvement of Traffic Flow and Delay at Eko-Ende Intersection in Ikirun, Osun State, Nigeria - SUBAIR, Sulaiman Olayinka; IBITOYE, Biliyamin Adeoye; KURANGA, Abdulrauf Toyin (ABUAD Journal of Engineering and Applied Sciences, 2024)
The rapid increase in traffic volume in Ikirun has led to rising congestion across the town’s road network. Stop delay, a significant indicator of intersection performance, is commonly used to assess the level of service (LOS) and capacity. This study investigated delays at the Eko-Ende intersection, a critical point in Ikirun’s traffic system that connects commercial hubs such as Ikirun Garage, Osogbo-Ilorin Road, Monday Market, and Alamisi Market. A geometric evaluation of the intersection showed approach widths of 7.2 m for Moshadek, 7.0 m for Kereje, 10.73 m for Sawmill, and 14.8 m for Nazeem. Traffic volume assessments revealed Sawmill as the busiest approach, with a weekly average peak-hour volume of 1,773 vehicles, followed by Moshadek and Kereje with 1,553 and 1,362, respectively, while Nazeem had the lowest volume at 876. The average peak-hour volume across the intersection was 5,566 vehicles. Delay studies indicated Sawmill had the highest delay (14.7 s), while Moshadek had the lowest (8.8 s), with an overall intersection LOS of B.